A comparative study on the quantum-dot-sensitized, dye-sensitized and co-sensitized solar cells based on hollow spheres embedded porous TiO2 photoanodes. (10th August 2015) - Cui, Can; Qiu, Yiwei; Zhao, Jiahuan; Lu, Bingqing; Hu, Haihua; Yang, Yana; Ma, Ni; Xu, Sheng; Xu, Lingbo; Li, Xiaoyun
Graphical abstract: Highlights: TiO2 hollow spheres (THS) affect light harvesting and electron transport in photoanodes. Three sensitization methods are applied for THS embedded photoanodes. Photovoltaic performance highly depends on THS content and sensitizer. Abstract: TiO2 hollow spheres (THS) of 400 nm in diameter are mixed into TiO2 nanoparticles film as light scattering centers to improve the light harvesting and photovoltaic performance of solar cells based on CdS quantum-dot sensitized TiO2 (TiO2 /CdS), N719 dye-sensitized TiO2 (TiO2 /N719) and CdS/N719 co-sensitized TiO2 (TiO2 /CdS/N719) photoanodes, respectively. The light harvesting and photovoltaic performance of the three types of solar cells are highly dependent on the THS content in TiO2 films due to: (1) the significant light scattering among or within THS, (2) the extended pore size distribution, and (3) the modulated electron transport in the TiO2 films. The optimal content of THS is around 10% by weight for TiO2 /CdS and TiO2 /CdS/N719 solar cells, and is around 15% for TiO2 /N719 solar cell. It is suggested that, in TiO2 /CdS and TiO2 /CdS/N719 solar cells, high content THS can facilitate the aggregation of large CdS nanocrystals, which limits the injection of photo-generated electrons from CdS to TiO2 due to serious internal recombination loss, and thus decreases the power conversion efficiency. The co-sensitized solar cell with the optimal THS content exhibits higher power conversion efficiency compared to the single-component sensitized solar cells.